THE ROLE OF SERUM AND LOCAL IgE CONCENTRATION IN QUALITY OF LIFE IN ALLERGIC RHINOSINUSITS PATIENTS - A. Vlaykov; D. Mihaylov; V. Stoyanov; M. Platikanova (Trakia Journal of Sciences)
Purpose: The task we set was to determine the concentrations of IgE molecules in serum and nasal lavage in patients with intermittent and persistentallergic rhinitis (AR) and to compare them with a control group of healthy volunteers, comparing the results with a quality of life questionnaire about their subjective feeling of potential health damage. Material and methods:: A comparison was performed between serum and nasal lavage IgE concentration in 50 participants - 40 cases and 10 controls. Results: Serum level of IgE-total in the patients with intermittent (AR) was 284,19 IU/ml while in persistent (AR) patients - 215,29 IU/ml, but not significantly higher than in the controls -160,87 IU/ml. IgE antibodies in nasal lavage in IAR patients was 1,39 IU/ml, while in PAR was 1,65 IU/ml and 1,05 IU/ml in controls.Total score of SNOT-22 in IAR (2,16) and PAR (2,03) was significantly higher than in the controls (0,85). Conclusions:In our study, although the different serum levels of IgE among groups, we did not find significant correlation between the concentration of IgE antibodies in blood serum or nasal lavage and the degree of impairment of the quality of life in patients with IAR and PAR assessed by SNOT-22 quality of life test.